Analisis Kepercayaan, Kualitas Layanan, dan Citra Lembaga Terhadap Keputusan Menabung di Bank Jateng Syariah KCPS Boyolali (Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the influence of trust, service quality, and institutional image on saving decisions at Bank Jateng Syariah KCPS Boyolali. The method used in this research is quantitative analysis with a survey approach. Data were collected through the distribution of questionnaires to 100 customers of Bank Jateng Syariah KCPS Boyolali. Data analysis was carried out using multiple linear regression techniques. Trust, service quality, and institutional image have a positive and significant influence because they directly shape customers’ sense of security, comfort, and confidence in managing their funds. Trust is the most dominant factor, as customers will only save when they feel their funds are secure, managed transparently, and in accordance with Islamic principles. Service quality strengthens this decision through experiences that are easy, fast, and responsive, making customers feel valued and well-assisted. Meanwhile, institutional image creates a perception of professionalism, credibility, and a strong reputation, which reduces doubts and increases customers’ pride in being part of the bank. The combination of these three factors encourages both rational and emotional confidence in customers to choose and continue saving. This study provides implications for bank management to continuously improve customer trust, service quality, and institutional image in order to attract more customers to save.